Nationwide Statistical Analysis of Lymphoid Malignancies in Korea - Lee, Hyewon; Park, Hyeon Jin; Park, Eun-Hye; Ju, Hee Young; Oh, Chang-Mo; Kong, Hyun-Joo; Jung, Kyu-Won; Park, Byung-Kiu; Lee, Eunyoung; Eom, Hyeon-Seok; Won, Young-Joo (Cancer research and treatment, 2018)
Regional differences in the incidence of lymphoid malignancies have been reported worldwide, but there has been no large-scale epidemiologic analysis in Korea. The aim of this study was to provide a nationwide population-based statistical analysis of Korean patients with lymphoid malignancies. The Korea Central Cancer Registry analyzed the incidence and survival of patients with lymphoid malignancies from the Korean National Cancer Incidence Database. Diseases were grouped by clinically relevant categories based on the 2008 World Health Organization classification. Overall 65,948 lymphoid diseases were identified between 1999 and 2012. The incidence of most subtypes increased with age, except for precursor cell neoplasms. Male predominance (male:female ratio=1.28:1) was observed. In 2012, annual age-standardized incidence rates per 100,000 persons of Hodgkin's lymphoma, mature B-cell neoplasm, mature T/natural killer (NK)-cell neoplasm, and precursor cell neoplasm were 0.46, 6.60, 0.95, and 1.50, respectively, and they increased yearly from 1999. Composite Hodgkin's and non-Hodgkin's lymphomas were extremely rare. Survival improvement estimated using 5-year relative survival rate was observed in patients with Hodgkin's lymphoma (71.1%-83.0%), diffuse large B-cell lymphoma (49.5%-61.5%), plasma cell neoplasms (20.2%-36.9%), and lymphoblastic lymphoma/leukemia (41.5%-56.3%) between 1993 and 2012. However, survival rates of T/NK-cell lymphoma (excluding cutaneous T-cell lymphoma) ranged from 40.5%-43.5% during the study period. Survival rates decreased with age in most subtypes. This report presented the subtype-specific statistical analysis of lymphoid malignancies in the Korean population, showing increasing incidences and survival rates in most subtypes.